Posted by **bob** on Saturday, March 10, 2012 at 3:27pm.

(4.35E-2 - x)(7.56E-2 -x )

============================

(0.324 + 2x)2

Rearrange to get an expression of the form ax2 + bx + c = 0 and use the quadratic formula (solve for x. This gives:

x = 1.05E-2, 0.143

basically i understand they use the quadratic equation but how did they change that crazy fraction into the quadratic formula?

- math -
**Damon**, Saturday, March 10, 2012 at 5:40pm
If that fraction = 0 (you left that out) then the denominator is not part of the problem unless it is zero.

32.88 E-4 - 11.91 E-2 x + x^2 = 0

x = [ 11.91E-2 +/- sqrt(142 E-4 - 132 E-4) ] / 2

= [ .119 +/- E-2 sqrt(10) ]/2

= [.119 +/- .031 ]/2

= .075 or -.044

- math -
**trevor **, Tuesday, March 13, 2012 at 12:37pm
for the following population of n=9 scores below.

11 12 16 15 19 16 13 17 11

range........

variance standard deviation s:

## Answer This Question

## Related Questions

- Math - Quadratic - Rearrange this expression into quadratic form, ax2 bx c = 0...
- Math - Rearrange this expression into quadratic form, ax2 bx c = 0 0.20= ((x^2...
- Math - Use the quadratic formula to solve each of the following quadratic ...
- Math - Stupid question time. I need to figure out how to rearrange equations to ...
- Algebra 2 help!!! - What value completes the square for the expression? x2 + 14x...
- math - A company has sales (measured in millions of dollars) of 50, 60, and 75 ...
- algebra - how would i work out the following problems solve each formula in ...
- math,algebra - can someone help me out factor out this 0=16t^2-122t+180 i have ...
- math - Solve the quadratic equation ax2+bx+c=0 using the completing the squares
- College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...

More Related Questions